Characteristics of lesser prairie-chicken (Tympanuchus pallidicinctus) long-distance movements across their distribution - Earl, J. E.; Fuhlendorf, S. D.; Haukos, David A.; Tanner, A. M.; Elmore, D.; Carleton, S. A. (My University, 2017)
Long-distance movements are important adaptive behaviors that contribute to population, community, and ecosystem connectivity. However, researchers have a poor understanding of the characteristics of long-distance movements for most species. Here, we examined long-distance movements for the lesser prairie-chicken (Tympanuchus pallidicinctus), a species of conservation concern. We addressed the following questions: (1) At what distances could populations be connected? (2) What are the characteristics and probability of dispersal movements? (3) Do lesser prairie-chickens display exploratory and round-trip movements? (4) Do the characteristics of long-distance movements vary by site? Movements were examined from populations using satellite GPS transmitters across the entire distribution of the species in New Mexico, Oklahoma, Kansas, and Colorado. Dispersal movements were recorded up to 71 km net displacement, much farther than hitherto recorded. These distances suggest that there may be greater potential connectivity among populations than previously thought. Dispersal movements were displayed primarily by females and had a northerly directional bias. Dispersal probabilities ranged from 0.08 to 0.43 movements per year for both sexes combined, although these movements averaged only 16 km net displacement. Lesser prairie-chickens displayed both exploratory foray loops and round-trip movements. Half of round-trip movements appeared seasonal, suggesting a partial migration in some populations. None of the long-distance movements varied by study site. Data presented here will be important in parameterizing models assessing population viability and informing conservation planning, although further work is needed to identify landscape features that may reduce connectivity among populations. © 2016 Earl et al.
Citation: Earl, J. E., Fuhlendorf, S. D., Haukos, D., Tanner, A. M., Elmore, D., & Carleton, S. A. (2016). Characteristics of lesser prairie-chicken (Tympanuchus pallidicinctus) long-distance movements across their distribution. Ecosphere, 7(8). doi:10.1002/(ISSN)2150-8925
Keywords: Dispersal; Foray Loop; Migration; Southern Great Plains; Tortuosity